2013
DOI: 10.1007/s00264-013-1868-7
|View full text |Cite
|
Sign up to set email alerts
|

Fresh-stored osteochondral allografts for the treatment of femoral head defects: surgical technique and preliminary results

Abstract: Purpose The purpose of this study was to present the preliminary clinical and radiographic outcomes of the treatment of femoral head osteochondral defects in eight consecutive symptomatic patients with fresh-stored osteochondral allografts via a trochanteric osteotomy. Methods This study included all consecutive patients treated in our department between 2008 and 2010 for worsening pain and mechanical symptoms of femoral head osteochondral defects. Each patient had preoperative routine hip radiographs and a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…A modified trochanteric slide osteotomy was used to expose the hip joint, as unstable pertrochanteric fractures with fracture lines at or below the rough line of the greater trochanter (AO/OTA Type A2.2, A2.3 and A3) are particularly amenable to this approach [15]. The trochanteric slide osteotomy has been developed specifically for complex arthroplasty procedures and provides excellent exposure for complex arthroplasty surgery [16,17]. Briefly, a coronal oriented osteotomy commencing lateral to the insertion of the posterior capsule and external rotators is performed using an oscillating saw.…”
Section: Surgical Technique For Arthroplastymentioning
confidence: 99%
“…A modified trochanteric slide osteotomy was used to expose the hip joint, as unstable pertrochanteric fractures with fracture lines at or below the rough line of the greater trochanter (AO/OTA Type A2.2, A2.3 and A3) are particularly amenable to this approach [15]. The trochanteric slide osteotomy has been developed specifically for complex arthroplasty procedures and provides excellent exposure for complex arthroplasty surgery [16,17]. Briefly, a coronal oriented osteotomy commencing lateral to the insertion of the posterior capsule and external rotators is performed using an oscillating saw.…”
Section: Surgical Technique For Arthroplastymentioning
confidence: 99%
“…The procedure does appear to improve the Harris hip scores [5] , [6] . Kosashvili et al [6] reported on eight patients with up to 24-months follow up and showed a 26.2 average improvement in Harris hip scores. Six out of eight (75%) patients had “good mobility” and had functional grafts at 42 months.…”
Section: Discussionmentioning
confidence: 90%
“…Osteochondral allograft (OCA) transplantation has been extensively used and studied for the treatment of large articular defects of the human knee with good to excellent long-term results reported [1] , [2] , [3] . OCA transplantation for the treatment of femoral-head defects in human patients has also been described, but only in the form of case reports or small case series [4] , [5] , [6] , [7] . The largest case series in the peer-reviewed literature is from 1985, and reported that OCA transplantation of the femoral head for the treatment of post-traumatic femoral-head defects, avascular necrosis without segmental collapse, osteochondritis dissecans, and tumours to be associated with an 80% long-term success rate in patients who did not have a steroid-related aetiology [7] .…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported on the results of eight of the patients included in the present study. 29 We concluded in this earlier study, that the patient with intractable post-allograft pain and progressive degenerative changes, who ultimately went on to conversion to THR six months after allograft, was a poor candidate for osteochondral allograft because of her longterm steroid use. We suggested at the time that steroidinduced AVN may predispose a patient to failure with an osteochondral allograft as the host bone may not be amenable to graft osteointegration due to diffuse metabolic damage, subchondral bone sclerosis and compromised vascularity.…”
Section: Discussionmentioning
confidence: 93%